2019
DOI: 10.1002/hed.25654
|View full text |Cite
|
Sign up to set email alerts
|

Not CD68 but stabilin‐1 expression is associated with the risk of recurrence in patients with oral cavity squamous cell carcinoma

Abstract: Background: This study's aim was to identify CD68 and stabilin-1 expressions and their prognostic implications in patients with oral cavity cancer (OCC). Methods: Stabilin-1 and CD68 immunochemical staining was conducted in samples from patients with OCC who underwent curative surgery in our institute. We retrospectively analyzed patients' clinical information. We investigated the relationship between CD68 and stabilin-1 expression levels and their effect on prognostic factors and survival. Results: Fifty-four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Some studies showed that high CD68 + macrophage associated with poor survival of OSCC ( 23 27 ) or with favorable survival of OSCC ( 28 ). Consistent with our results, there are also studies demonstrated no association of CD68 + macrophage infiltration with prognosis of OSCC patients ( 29 , 30 ). However, we observed a poor OS and a poor DFS in radiation treated OSCC patients with high CD68 + macrophage infiltration, especially in HPV negative subgroup, but not in HPV positive subgroup.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies showed that high CD68 + macrophage associated with poor survival of OSCC ( 23 27 ) or with favorable survival of OSCC ( 28 ). Consistent with our results, there are also studies demonstrated no association of CD68 + macrophage infiltration with prognosis of OSCC patients ( 29 , 30 ). However, we observed a poor OS and a poor DFS in radiation treated OSCC patients with high CD68 + macrophage infiltration, especially in HPV negative subgroup, but not in HPV positive subgroup.…”
Section: Discussionsupporting
confidence: 92%
“…42 Similarly, in another cohort of patients with bladder cancer, intratumoural Clever-1 TAM density is an independent prognostic factor for poor overall survival, 43 and increases the risk of recurrence in patients with oral cavity cancers. 44 Gene expression analyses using multiple datasets have also identified high STAB1 expression as a prognostic factor for poor outcome in patients with cytogenetically normal acute myeloid leukaemia (CN-AML). 45 The same study shows that not only does Clever-1 suppression in AML cell lines (KG-1 and NB4) inhibit their proliferation, but it also makes them more sensitive to the BCL2 inhibitor, venetoclax, resulting in increased apoptosis of the cells.…”
Section: Clever-1 In Immunosuppression and Cancermentioning
confidence: 99%
“…This notion is also supported by data showing that targeting Clever-1 in combination with anti-PD-1 in refractory (immunologically cold, such as colon [CT26] and triple-negative breast [4T1]) tumour models improves treatment efficacy. 47 Relatively few reports have been published addressing Clever-1 expression as a predictive or prognostic factor for patient outcome, 40,41,43,44 and there are no reports of Clever-1 expression during ICI treatments; we, therefore, sought to investigate the significance of Clever-1 expression (at the mRNA level) in immunotherapy resistance, T-cell exclusion and dysfunction by extracting data from publicly available clinical datasets. Generally, a high expression of STAB1 in cancer patients of The Cancer Genome Atlas pan-cancer cohort (n = 11768) is significantly associated with reduced survival, regardless of patient characteristics, tumour type, therapy or clinical manifestations (Fig.…”
Section: Association Of Clever-1 With Immunotherapy Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…However, in more advanced satges (Stage IV), patients with a high number of peritumoral or intratumoral Stabilin-1 macrophages showed a shorter disease-specific survival (p=0.05, and p=0.008, respectively) [28]. In addition, previous studies have reported that Stabilin-1 is associated with the prognosis of bladder urothelial carcinoma and oral squamous cell carcinoma [29,30]. Riabov V demonstrated that Stabilin-1 is expressed on tumor-associated macrophages (TAM) in human breast cancer, and with higher expression levels recorded in stage I [31].…”
Section: Discussionmentioning
confidence: 98%